Decompressive Craniectomy in Patients with Malignant Stroke with Additional Vascular Territory - Sampaio, Raul Pansardis [UNESP]; Fogaroli, Marcelo Ortolani [UNESP]; Botta, Fabio Pires [UNESP]; Módolo, Gabriel Pinheiro [UNESP]; Luvizutto, Gustavo José; Betting, Luiz Eduardo [UNESP]; Zanini, Marco Antônio [UNESP]; Bazan, Rodrigo [UNESP]; Hamamoto Filho, Pedro Tadao [UNESP] (Elsevier, 2024)
Background: Decompressive craniectomy substantially reduces mortality and disability rates following a malignant stroke. This procedure remains a life-saving option, especially in contexts with little access to mechanical thrombectomy despite downward trends in the performance of decompressive craniectomy due to discussions on the acceptance of living with severe disabilities. However, the outcomes of the surgery in cases involving concomitant occlusion of anterior or posterior cerebral arteries have not been extensively studied. Methods: In this retrospective cohort study, spanning January 2010 to December 2022 and including patients who underwent decompressive craniectomy, we compared outcomes between patients with and without additional vascular territory involvement. Independent variables included age, sex, comorbidities, admission National Institutes of Health Stroke Scale and Glasgow Coma Scale scores, time elapsed between stroke and surgery, laterality of the stroke, midline shift, and postoperative infarction volume. Outcomes included mortality and modified Rankin Score at the 3-month follow-up. Results: Of the 86 patients analyzed, 61 (70.9%) and 25 (29.1%) demonstrated no territory and additional territory involvement, respectively. Patients with involvement of additional territories exhibited lower admission Glasgow Coma Scale scores, higher National Institutes of Health Stroke Scale scores, and larger postoperative infarction volumes. However, these variables were not associated with poor outcomes. Univariate analyses revealed no differences in mortality or severe disability. Even after adjustment, the differences remained insignificant for mortality and severe disability. Age emerged as the sole variable linked to increased mortality. Conclusions: Our data suggest that, for patients with malignant stroke undergoing decompressive craniectomy, the outcomes for patients with and without involvement of additional vascular territory are similar.
Keywords: Acute ischemic stroke; Cerebral arteries; Decompressive craniectomy; Survival